Synthesis and crystal structures of 6- and 8-methyl-3-phenylbenzo[e][1,2,4]triazines - Christos P. Constantinides; Syed Raza; Fadwat Bazzi; Nisreen Sharara; Simona Marincean (Acta Crystallographica Section E: Crystallographic Communications)
The synthesis and single-crystal X-ray structures of two regioisomeric Blatter radical precursors, 6-methyl-3-phenylbenzo[e][1,2,4]triazine, (I), and 8-methyl-3-phenylbenzo[e][1,2,4]triazine (II), C14H11N3, are reported. Both compounds feature planar heteroaromatic frameworks with extensive π-conjugation across the benzo[e][1,2,4]triazine core. Compound I crystallizes in the orthorhombic space group Pbca, while II adopts the monoclinic space group P21/c. Structural analysis reveals nearly identical bond lengths and angles across both isomers, indicating minimal influence of methyl substitution on core geometry. Supramolecular features are dominated by π–π stacking interactions, leading to one-dimensional columnar arrangements. Compound I exhibits alternating dimers with slippage in both stacking directions and forms hydrogen-bonded chains that generate dense, wave-like sheets. Compound II displays uniform stacking with regular interplanar distances and pronounced translational overlap. These structural insights contribute to understanding how regioisomeric substitution patterns influence the solid-state organization of Blatter radical precursors, with implications for their application in molecular electronics and spin materials.